Interpretasi Kaidah Arsitektur Islam Pada Desain Rumah Tradisional Aceh - Annisa, Astrid; Ali Nasution, Mufti (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Abstract. Aceh, as a province deeply rooted in Islamic Sharia, consistently applies the teachings of Islam in every aspect of community life. Aceh has customs and culture based on Islamic teachings. Traditional Acehnese houses, commonly known as 'Rumoh Aceh,' represent the traditional homes of the Acehnese people, conveying meanings and philosophies related to the culture and customs of the Acehnese community. This research aims to identify and examine the compatibility of traditional Acehnese house designs based on Islamic values and architectural principles. The study employs a descriptive-qualitative method to uncover the application of Islamic architecture in traditional Acehnese house structures. The research findings indicate that traditional Acehnese houses adhere to Islamic architecture principles. Every element of the building and the design of spaces, all grounded in the teachings of Islam.